Effects of the environment on the conformational stability of the chloride intracellular channel protein CLIC1 - McIntyre, Sylvia (My University, 2008)
CLIC1 is an intracellular membrane protein that is unusual in that it can exist in both a soluble and an integral membrane form. The manner in which this protein inserts into membranes is unknown although it is proposed to undergo a change in structure whereby it initially experiences a degree of unfolding and then refolds into its new membrane-bound conformation. This study focuses on the characterisation of CLIC1 in terms of its secondary, tertiary and quaternary structure, the determination of its conformational stability at equilibrium and the establishment of its unfolding kinetics, all under conditions of varying pH, polarity, redox conditions, temperature and ionic strength. CLIC1 was found to be most stable at pH 7.0 / 20oC. The unfolding process is two-state and cooperative, producing a DG(H2O) of ~10 kcal/mol and a m-value of ~2 kcal/mol per molar urea. A decrease in pH to 5.5 or an increase in temperature to 37oC resulted in the stabilisation of an equilibrium intermediate species under mild denaturing conditions and a destabilisation of the native state. This was further evidenced by an increase in the rate of unfolding of CLIC1 from the native state to the denatured state under these conditions. A state with similar properties to the intermediate species was detected in the absence of urea at pH 5.5 / 37oC and under non-reducing conditions at both pH 7.0 / 20oC and pH 5.5 / 20oC. The intermediate species is more hydrophobic than either the native or denatured state; it is stabilised by salts, has a reduced secondary structure, increased flexibility and a buried Trp35 relative to the native state. The rate of formation of the intermediate species is a slow process which may involve an oligomerisation step. The results from this study provide an interpretation for the structure and mechanism of CLIC1 pore formation in vivo by comparing the effects of the environment on the structure and stability of the protein.
Keywords: stability; folding; kinetics; intermediate; GST; CLIC1; Molten globule; pH; electrostatics; ANS; Redox; polarity; membrane; toxin; Bcl